Caracterização clínica e anatomopatológica da infecção por haemophilus parasuis sorovar 7 cepa 174 em leitões privados de colostro - Dazzi, Cláudia Cerutti (2018)
Haemophilus parasuis, the ethiological agent of Glässer disease, is a Gram-negative coccobacilli of the Pasteurelaceae family. Glässer disease is a systemic infection characterized by deposition of fibrinous to fibrinosuppurative material in the joints, serosal surfaces and meninges. Currently, there are 15 typeable serovars (SV) known and classified according to virulence in highly and moderately virulent and avirulent. Since 1992, SV 7 reference strain 174 has been considered an avirulent to mildly virulent sorovar. However, in recent years, SV7 has been increasingly isolated not only from lungs, but also from systemic sites such as joints in pigs with classical symptoms of Glässer disease. These findings led us to believe that SV7 might be virulent and able to cause Glässer’s disease. To confirm our hypothesis, twenty colostrum-deprived piglets were intratracheally challenged with 1x10 7 Haemophilus parasuis SV 7, strain 174. Infected piglets had clinical signs consistent with Glässer disease. One piglets died by septic shock in less than 24h post-infection. After 24h, infected piglets had fever (over 40ºC), associated firstly with arthritis and then with respiratory signs. With the progression of the disease, at the second and third day post-infection, piglets had neurological signs, arthritis and dyspnea and none of the infected piglet survived after the fifth day post-infection. All piglets were necropsied and tissue samples collected for bacteriological and histopathological analyses. Haemophilus parasuis was isolated in chocolate agar and the identity of the SV was confirmed by a multiplex PCR. The main macroscopic findings were polyarthritis, polyserositis and meningitis which are the classical signs of Glässer Disease. Microscopically, these lesions were characterized by neutrophilic and macrophage infiltration in a fibrinous net (fibrinosuppurative infiltrate), associated to few lymphocytes. In addition, we observed thymic aplasia and fibrinosuppurative endophthalmitis. Based on the anatomopathological findings, we observed the possibility of H. parasuis overcome hematological barriers in organs such as cerebrum, eye and thymus. We observed ocular lesions in several piglets, yet not described for Glässer Disease, characterized by endophthalmitis and perineuritis of the ocular nerve. With this study we concluded that SV7 strain 174 is capable of causing Glässer disease in highly susceptible piglets and that the classification of this SV should change from avirulent to virulent.